2019
DOI: 10.1002/mc.23109
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CCAT1 is a biomarker for the proliferation and drug resistance of esophageal cancer via the miR‐143/PLK1/BUBR1 axis

Abstract: Recent evidence indicates that long noncoding RNA colon cancer‐associated transcript‐1 (lncRNA CCAT1) is abundantly expressed in esophageal cancer and is closely related to the occurrence, development, invasion, metastasis, and drug resistance of this disease. However, the role and molecular mechanisms of CCAT1 in the cell proliferation and chemoresistance of esophageal cancer are largely unknown. The correlation between CCAT1 expression and drug resistance to cisplatin (CDDP) in esophageal squamous cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 31 publications
(65 reference statements)
1
42
0
Order By: Relevance
“…5). CCAT1 seRNA is proved to be a significant biomarker in CRC, abundant studies have proved that it is also upregulated in different cancers, such as bladder cancer [73], esophageal cancer [74], cervical cancer [74], prostate cancer [103], and ovarian cancer [75]. In particular, squamous cell carcinoma (SCC) specific SE regions are cooperatively occupied with TP63 and SOX2 to boost CCAT1 seRNA transcription, CCAT1/TP63/SOX2 complex is bound to SE regions of epidermal growth factor receptor (EGFR) to promote EGFR transcription.…”
Section: Serna Promotes Oncogene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). CCAT1 seRNA is proved to be a significant biomarker in CRC, abundant studies have proved that it is also upregulated in different cancers, such as bladder cancer [73], esophageal cancer [74], cervical cancer [74], prostate cancer [103], and ovarian cancer [75]. In particular, squamous cell carcinoma (SCC) specific SE regions are cooperatively occupied with TP63 and SOX2 to boost CCAT1 seRNA transcription, CCAT1/TP63/SOX2 complex is bound to SE regions of epidermal growth factor receptor (EGFR) to promote EGFR transcription.…”
Section: Serna Promotes Oncogene Expressionmentioning
confidence: 99%
“…5). CRC-specific seRNA CCAT1-L has been proved to be overexpressed in various cancers including bladder, cervical and ovarian cancer, it promotes EMT activation, invasion and metastasis [73][74][75]. seRNA HCCL5 is considered as an SE-driven cytoplasmic lncRNA in HCC, and it accelerates EMT phenotype, invasion and metastasis in HCC cells by up-regulating Snail, Slug, ZEB1 and Twist1 expression [72].…”
Section: Serna Mediates Emt Of Cancer Cellmentioning
confidence: 99%
“…A total of 10 hub genes, including AURKA, PLK1, TPX2, CDC6, FOXM1, TRIP13, RAD51AP1, ECT2, SPAG5, and CKS1B, were obtained from the PPI network of 93 overlapping DEGs in GSE92396, GSE17351, and GSE9982 datasets (Figure 1). It had been reported that AURKA [22], PLK1 [23], TPX2 [24], FOXM1 [25], TRIP13 [26], and CKS1B [27] were closely related to the development and progression of ESCC. However, the effects of CDC6, RAD51AP1, ECT2 and SPAG5 on the proliferation, apoptosis, invasion, migration and chemotherapy resistance in ESCC has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of non-proteincoding transcripts longer than 200 nucleotides in length. Dysregulation of some lncRNAs promotes cellular processes related to cancer, including proliferation, invasion, metastasis, apoptosis, and drug resistance (Lu et al, 2017;Guan et al, 2019;Hu et al, 2019;Wang et al, 2019). Therefore, lncRNAs are considered a group of promising markers for predicting cancer prognosis and developing new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%